ZnO thin film as non-enzymatic glucose sensor in an alkaline solution (Superficies y Vacío, 2019)
In this work, ZnO films were deposited on titanium substrates by the sputtering technique for non-enzymatic glucose detection in an alkaline solution. The samples were grown using pulsed D.C. sputtering using a ZnO target; we remain constant the power at 100 W and varied the deposition time in order of obtain films with different thickness.  The properties of the samples were analyzed by X-ray diffraction (XRD), optical transmission, scanning electron microscopy (SEM), and electrochemical techniques. The results shown that the thickness of the samples varied with the deposition time. The electrochemical response studied by cyclic voltammetry revealed that the sensor response increased when the ZnO film thickness decreased. The electrochemical biosensing device showed a sensitivity of 7.65 ?A cm-2mM-1 with a linear response range of 3.3 mM to 11.0 mM.